AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH: APAKAH AKSESIBILITAS, PENGENDALIAN INTERNAL, DAN KOMPETENSI APARATUR MEMPENGARUHINYA - Luqyana, Luqyana; Islahuddin, Islahuddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the influence of accessibility of financial statement, governments internal control system, and apparatus competence on the accountability of regional financial management in Regency/City Governments in The Province of Aceh. The research was conducted in municipalities of Aceh Barat, Aceh Besar, Aceh Tengah, City of Banda Aceh and Lhokseumawe. Representatives of municipalities/cities are determined randomly by looking at the geographical location of the area. Data was collected by distributing 70 research questionnaires to respondents, The Head of SKPD. The research questionnaires that were received back amounted to 62 questionnaires. The sampling technique used simple random sampling and analyzing the data obtained using multiple linear regression models facilitated by SPSS version 28. The results which were based on 62 responses show that (1) accessibility of financial statement has an effect on accountability of regional financial management, (2) governments internal control system has no effect on the accountability of regional financial management, (3) apparatus competence has an effect on accountability of regional financial management, and (4) accessibility of financial statement, government internal control system, and apparatus competence simultaneously effect the accountability of regional financial management.